THE ROLE OF THE TRANSFORMATIONAL TEACHER PROGRAM IN FOSTERING TEACHER COLLABORATION - Awi Ria; Ujang Jamaludin; Suharjuddin Suharjuddin (Jurnal Eduscience)
Purpose–This research aims to analyze the impact of the Transformational Teacher Program on enhancing teacher collaboration competence in elementary schools in Bekasi City. Teacher collaboration is a critical skill in addressing the demands of 21st-century education. The program is designed to develop teachers as learning leaders who can collaborate and innovate within professional learning communities.